Implementasi Pendekatan Pedagogi Dalam Meningkatkan Kecerdasan Sosial Pada Peserta Didik Kesetaraan Paket A Di Homeschooling Kak Seto Surabaya - Adhiansyah, Doni; Susilo, Heryanto (J+PLUS UNESA, 2024)
This study aims to analyze and describe the Implementation of Pedagogical Approaches in Improving Social Intelligence in Package A Equality Students at Kak Seto Surabaya Homeschooling. This research method is a descriptive qualitative type. The data analysis techniques used are data collection, data reduction, data presentation, and conclusion drawn. The results of the research can be obtained from the Implementation of Pedagogical Approaches in Improving Social Intelligence in Package A Equality Learners At Homeschooling Kak Seto Surabaya is an approach that focuses on creating an inclusive and responsive environment that supports the development of students' social and academic skills, preparing them for future social and professional challenges through interactive and collaborative methods. And social intelligence in Kak Seto Surabaya's Homeschooling involves the ability to interact, work together, and understand others in a communal environment. It strengthens the relationship between students and tutors, facilitates collaborative learning, and prepares students for community life through self-awareness, cooperation, communication, empathy, and problem-solving.